Program Studi Pendidikan Matematika Fakultas Keguruan dan Ilmu Pendidikan Universitas Pasir Pengaraian - -, Juniza; -, Arcat; -, Hardianto (Jurnal Ilmiah Mahasiswa FKIP Prodi Matematika, 2015)
This research aims to determine whether there was an effect Think Pair Share cooperative learning model formathematics learning outcomes. This type of research is a quasi-experimental, the population it is a class IXJunior high school 1 Kepenuhan Hulu. The sampling technique used is saturated sample technique, whichmeans the population as well as the sample. Grade sample consisted of experimental class and control class,which applied the experimental class learning model TPS while the control class applied conventional learningmodel. Instrument used instrument test is test essay. and the done hypothesis testing used t test its calculationresults obtained t = 2.174 and table = 2.026 which means t hitung > t table at 5% significance level, thehypothesis is accepted